Preparation and tunable optical properties of amorphous AlSiO thin films. (May 2021) - Magnusson, Roger; Paul, Biplab; Eklund, Per; Greczynski, Grzegorz; Birch, Jens; Jonson, Bo; Ali, Sharafat
Abstract: Thin films in the aluminosilicate (AlSiO) system containing up to 31 at. % Al and 23 at. % Si were prepared by reactive RF magnetron co-sputtering in order to investigate the dependence of film formation and optical properties on substrate temperature and Si and Al contents. The obtained films were amorphous with smooth microstructure. The growth rate at different substrate temperatures ranged from 1.2 to 3.3 nm/min and increase with increasing the Si target power. The roughness decreases and thickness increases with increasing Si content. The thickness of the films grown at a deposition temperature of 100 °C is found to be higher than the films deposited at 300 and 500 °C. The AlSiO-coated glasses have a higher transmission in the visible region than the uncoated glass. The spectroscopic ellipsometry analysis reveals that the refractive index value decreased with decreasing the Al content, having extinction coefficient values of zero in the measured spectral region and band gap values ≥ 3.4 eV. The obtained thin films have over 90% transmittance in the visible range and no systematic variation of transmittance was observed with substrate temperature. The results suggest that glass substrate coated with AlSiO thin films have improved optical properties. Highlights: AlSiO film (up to 400 nm thick) were synthesized by using RF magnetron sputtering of Al and Si metallic targets. AlSiO films have x-ray amorphous structure. The AlSiO films are stoichiometric and are not phase-separated. The glassy AlSiO films are smooth, having a typical surface roughness d E M A < 2 nm. AlSiO films exhibit 90% or more average light transmittance over the visible range.